CURRENT DEMAND FOR WATER RESOURCES IN EGYPTIAN AGRICULTURE - M. Ibrahim; S. Makled; A. Elsabea (Arab Universities Journal of Agricultural Sciences, 2019)
Water is one of the most important inputs and elements of development, and the importance of water in Egypt is increasing due to the lack of resources and increased demand in recent periods, where rain is scarce and covers most of its deserts. The River Nile is the main water supplier in the Arab Republic of Egypt, where the share of the river about 55.5 billion cubic meters per year, and the problem is limited to the study of the current and future use of water, while Egypt suffers from the constant amount of water available to cover these uses, The high rates of Egyptian population growth, with Egypt's share of water remaining constant, and hence the problem of water shortage, is a threat to the national economy in general and the agricultural sector in particular. The aim of the  study is to use water for the time being and to work to increase the efficiency of water use in future years The study shows that the quantities of water used in irrigation for agricultural crops in Aswan fluctuated between the minimum and the decrease, ranging between a minimum of about 40.1 billion m3 in 2012 and a maximum of about 62.1 billion M3 in 2008 with an annual average of about 50.48 billion m3 during the same period. And the study of the equation of the general time trend for the quantities of water used for irrigating agricultural crops in Aswan and it shows that there is no mathematical picture suitable for the nature of the data and that the data revolve around the mean arithmetic.